2015
DOI: 10.3945/jn.114.207472
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Dietary Patterns Describe Dietary Behavior across Ethnic Groups in the Netherlands, but Different Elements in the Diet Are Associated with Glycated Hemoglobin and Fasting Glucose Concentrations

Abstract: Although similar food group dietary patterns were derived within 5 ethnic groups, the association of the meat-and-snack pattern with fasting glucose concentrations differed by ethnicity. Taken together with the finding of ethnic differences in biomarker-driven dietary patterns, our results imply that addressing T2D risk in multiethnic populations requires ethnicity-specific approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 34 publications
(43 reference statements)
2
24
0
Order By: Relevance
“…higher fasting C-peptide concentrations and insulin resistance. Our results are in accordance with previous studies in people without diabetes, where dietary patterns characterized by high intake of refined foods, red meat, full-fat dairy, sweets, and snacks were adversely associated with glucose homeostasis, but not with body composition [ 29 , 30 ]. The absence of associations between the PCA dietary patterns and serum lipids in our study indicates that adverse food choices, as reflected by our PCA pattern 1, may be detrimental for glucose homeostasis rather than for serum lipid concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…higher fasting C-peptide concentrations and insulin resistance. Our results are in accordance with previous studies in people without diabetes, where dietary patterns characterized by high intake of refined foods, red meat, full-fat dairy, sweets, and snacks were adversely associated with glucose homeostasis, but not with body composition [ 29 , 30 ]. The absence of associations between the PCA dietary patterns and serum lipids in our study indicates that adverse food choices, as reflected by our PCA pattern 1, may be detrimental for glucose homeostasis rather than for serum lipid concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…The orthogonal (varimax) and oblique (oblimin) rotation methods gave the same result, and we chose to apply the orthogonal (varimax) rotation method in order to achieve a simpler structure of the dietary patterns with greater interpretability. The varimax rotation is the most common rotation method applied in dietary pattern analysis (1,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and leads to uncorrelated dietary patterns. Food groups with a factor loading ≥0•3 (absolute value) were considered to be important contributors to a component.…”
Section: Methodsmentioning
confidence: 99%
“…This is in line with a previous study that showed an association between PTSD and metabolic risk factors (BMI, obesity rates, abdominal obesity and triglycerides) in white Americans, but not in African-Americans [ 15 ]. The results from this study lead us to suggest that in ethnic minority groups, the risk of developing the MetS may be more strongly influenced by other risk factors, such as depressive symptoms, disadvantageous biological factors that originate in early life [ 51 ] or ethnicity-specific dietary patterns [ 52 ] andexercise beliefs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%